Purchasing behaviour on halal food products during movement control order (MCO): quantitative evidence from covid-19 pandemic / Sharifah Zannierah Syed Marzuki ... [et al.] - Syed Marzuki, Sharifah Zannierah; Abdullah, Hasni; Ab. Halim, Roslilee; Buyong, Siti Zahrah; Zreik, Mohamad (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Public health issue on Coronavirus Disease (COVID-19) does not hinder Muslim followers from maintaining their religious conformance to Islamic Dietary Law when purchasing for halal food. To them, only food deemed as halal is fit for consumption. This study uses descriptive analysis to investigate mean readings to the predictive variables. A sample of 331 Muslim respondents have answered an online survey during Movement Control Order (MCO) that started on March 18, 2020 in Malaysia. Quantitative evidence shows that respondents are very particular and want to ensure that the food products they will consume come from halal sources. In addition, they do not tolerate with consumer products without the halal logo. The study concludes with a discussion on the importance of religiosity, access, supplies, halal certification and halal logo in a Muslim purchasing behaviour during the global crisis of the current pandemic of COVID-19.